New decentralized nonlinear voltage controller design for power systems - Zhu, Chun Lei. (2009)
This research project focuses on the design of a new decentralized nonlinear voltage controller for power systems, which can achieve simultaneous voltage regulation and system stability enhancement, to replace the existing AVR and PSS combination. The main objectives of excitation systems are to achieve satisfactory voltage regulation and to improve system stability effectively. However, the conventional excitation controller design has two drawbacks.